The development of a discrete-event based simulation model to improve large diameter steel water pipeline construction processes - Wannenburg, Stefanie (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2018.